Effect of precision nitrogen management on yield and nitrogen use efficiency in different varieties of wheat (Triticum aestivum) - TYAGI, VISHAL; SINGH, R K; NAGARGADE, MONA (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during two consecutive winter (rabi) seasons of years 2015-16 and 2016-17 to study the effect of different nitrogen scheduling on yield and nitrogen use efficiency of different varieties of wheat (Triticum aestivum L.). The experiment was laid out in split-plot design with three replications; in which three varieties (viz. HUW 234, K 0307 and HD 2967) were planted in main plots. The combinations of 6 nitrogen scheduling practices which included different N application rates from 0 to 150 kg/ha in various split doses along with the use of LCC and Greenseeker was planned in sub plots. Results reveal that the yield attributing characters, grain yield, straw yield and biological yield were recorded significantly highest in HD 2967 as compared to other varieties. Whereas, varietal parameter did not significantly influence the agronomic efficiency, recovery efficiency and nitrogen harvest. Among nitrogen scheduling, application of 150 kg N/ha in three equal splits recorded significantly higher yield attributes, grain yield (4.70 and 4.81 t/ha), straw yield, biological yield, harvest index, and recovery efficiency of nitrogen. Greenseeker based nitrogen application recorded significantly highest agronomic efficiency and partial factor productivity of nitrogen.